2003
DOI: 10.1034/j.1600-0412.2003.00010.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma YKL‐40, as a prognostic tumor marker in recurrent ovarian cancer

Abstract: High plasma YKL-40 is related to short survival in patients with recurrent ovarian cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(42 citation statements)
references
References 27 publications
(37 reference statements)
2
40
0
Order By: Relevance
“…There was no relationship between serum YKL-40 levels and LDH and performance status of the patients. The percentage of patients with extensive SCLC with elevated serum YKL-40 is comparable to the percentage of patients with metastatic breast, colorectal and ovarian carcinoma with elevated serum YKL-40 [19][20][21][22][23][24]. The present study also showed that an elevated serum YKL-40 level at time of diagnosis reflected increased lung cancer aggressiveness since patients with high serum YKL-40 had shorter [19][20][21][22][23][24].…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…There was no relationship between serum YKL-40 levels and LDH and performance status of the patients. The percentage of patients with extensive SCLC with elevated serum YKL-40 is comparable to the percentage of patients with metastatic breast, colorectal and ovarian carcinoma with elevated serum YKL-40 [19][20][21][22][23][24]. The present study also showed that an elevated serum YKL-40 level at time of diagnosis reflected increased lung cancer aggressiveness since patients with high serum YKL-40 had shorter [19][20][21][22][23][24].…”
Section: Discussionsupporting
confidence: 57%
“…Increased serum YKL-40 levels are found in patients with primary and metastatic breast carcinoma [18][19][20] and ovarian carcinoma [21,22], and in preand post-operative samples from patients with colorectal carcinoma [23,24]. It was found in these studies that high serum YKL-40 levels were related to short recurrence-free interval and poor survival of the patients.…”
Section: Introductionmentioning
confidence: 61%
“…1 Both tumor cells and tumor-associated macrophages produce YKL-40. 2 Plasma YKL-40 is high in patients with gastrointestinal, [3][4][5] breast, 6 lung, 7 prostate 8 and other cancer, [9][10][11] and is also associated with tumour burden and prognosis after a cancer diagnosis. 5,[12][13][14][15][16] Furthermore, high plasma YKL-40 predicts high risk of gastrointestinal cancer in the general population.…”
mentioning
confidence: 99%
“…It was first isolated from porcine VSMC, which is highly induced during nodule formation, but the precise function of this gene is presently unknown. High serum expression of YKL-40 has been associated with poor prognosis in colorectal cancer (Cintin et al, 1999), glioblastoma multiforme (Tanwar et al, 2002), breast cancer (Johansen et al, 1995), ovarian cancer (Dehn et al, 2003), and lung cancer (Johansen et al, 2004). Consistent with the function of CLU, overexpression of YKL-40 has been implicated in increased migration and tissue remodeling.…”
Section: Discussionmentioning
confidence: 99%